Fat prefabrication using a fascial flap in the rat model - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2000)
Prefabrication of fat tissue using a fascial flap based on the superficial inferior epigastric artery was studied in rats. First, the superficial inferior epigastric fascia was transposed over the inguinal fat pad. Two weeks later fascia and fat were elevated together as a prefabricated composite flap. At this stage, a pilot study was done in ten rats and perfusion of the flaps was tested with fluorescein. After confirming fluorescein staining of the prefabricated flaps, the study continued with experimental and control groups of rats. In the experimental group, prefabricated flaps were transposed to the subcostal area. In the control group, the pedicles of the flaps were severed, creating composite grafts. These grafts were transferred to the subcostal area in the same manner as in the experimental group. One week later the flaps were re-elevated and grafts were exposed. Fluorescein tests and Indian ink microangiography were carried out. In the experimental group, the flaps were stained, while grafts in the control group were not stained. Fat and fascia were found to be viable in the experimental group, while they were necrotic in the control group on histopathological examination. Based on these findings, we can conclude that the prefabrication of fat by vascular fascia is successful and may have application in plastic surgery. (C) 2000 Harcourt Publishers Ltd.
Keywords: fascial flap; fat prefabrication; ADIPOSE-TISSUE; AUTOLOGOUS FAT; TRANSPLANTATION; GRAFT; RECONSTRUCTION; COMPOSITE; INJECTION; REVASCULARIZATION; AUGMENTATION; SURVIVAL